PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Pada PT Bank Rakyat Indonesia, Tbk. Cabang Pandanaran Semarang) - Sasongko, Mahar Nur; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2016)
The success of a company rely to human who carry out the work so that the success of an organization is strongly influenced by the performance of individual employees. BRI Branch Pandanaran Semarang is a company engaged in banking, especially those serving the provision of capital. In the operation of the activity BRI Branch Office Semarang Pandanaran always emphasize to all human resources to achieve good performance. Problems that occur in the PT. Bank Rakyat Indonesia, Tbk. The new branch will Pandanaran today is a decrease in employee performance evaluation of the results of employee performance objectives that are not in accordance with predetermined targets. Allegedly justice will affect the performance of the employee compensation with intrinsic work motivation as an intervening variable.The independent variables used is compensation, an intervening variable is the motivation and the dependent variable is the performance. The sample used in this study as many as 57 employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Semarang Pandanaran using proportional random sampling technique. The data used is primary data by questionnaire. The analysis technique used is the linear regression and test the mediating effect.Based on the results of the analysis can know that compensation and significant positive effect on employee performance. Compensation indirect effect on employee performance through motivation to work, so it can be concluded that the work motivation becomes a variable that mediates between equity compensation on employee performance.